2017
DOI: 10.1038/s41598-017-07979-y
|View full text |Cite
|
Sign up to set email alerts
|

The miR-183 family cluster alters zinc homeostasis in benign prostate cells, organoids and prostate cancer xenografts

Abstract: The miR-183 cluster, which is comprised of paralogous miRs-183, -96 and -182, is overexpressed in many cancers, including prostate adenocarcinoma (PCa). Prior studies showed that overexpression of individual pre-miRs-182, -96 and -183 in prostate cells decreased zinc import, which is a characteristic feature of PCa tumours. Zinc is concentrated in healthy prostate 10-fold higher than any other tissue, and an >80% decrease in zinc is observed in PCa specimens. Here, we studied the effect of overexpression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…The mechanism of stabilization could be explained by involving the amino groups of chitosan in the binding of zinc ions as well as ionic cross-linking with TPP molecules [ 76 ]. Although zinc is not used as a direct decoy for tumors in nanopharmaceuticals, several studies have pointed out the enhanced uptake of zinc ions in prostate cancer [ 80 , 81 ]. Normal prostate glands contain higher levels of zinc compared with cancerous tissues as well as the levels of MT.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of stabilization could be explained by involving the amino groups of chitosan in the binding of zinc ions as well as ionic cross-linking with TPP molecules [ 76 ]. Although zinc is not used as a direct decoy for tumors in nanopharmaceuticals, several studies have pointed out the enhanced uptake of zinc ions in prostate cancer [ 80 , 81 ]. Normal prostate glands contain higher levels of zinc compared with cancerous tissues as well as the levels of MT.…”
Section: Discussionmentioning
confidence: 99%
“…To further elucidate the regulatory mechanism of Erbin in AML, a bioinformatics method was employed to predict and screen the possible targets of Erbin, and miR-183-5p was found to bind directly to the 3′ UTR of Erbin. The function of miR-183 in tumors has been intensively reported; it often shows high expression in tumors, accompanied by allelic imbalance, chromosome breakage, and increased copy number, 11 , 12 , 13 , 14 , 15 , 16 , 17 and most of these phenotypes are manifested as carcinogenic. Some phenotypes also show tumor suppressor activity, suggesting that its tumorigenicity may be dependent on the environment and cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Ueno reported that miR-183 could target Dkk-3 and SAMAD4 and has an oncogenic biological behavior [ 17 ]. Due to the paralogous property of miR-183, miR-96, and miR-182, these three miRNAs have been studied as miR-183 cluster, which could regulate zinc levels and carcinogenic pathways in prostate cells [ 18 ]. MiR-96 was also reported enhancing PCa cell proliferation through FOXO1 [ 19 ], which could be speculated in the PPI network ( Figure 2(a) ).…”
Section: Discussionmentioning
confidence: 99%